Analysis of the in vitro activity of human neutrophils against Aspergillus fumigatus in presence of antifungal and immunosuppressive agents. (9th October 2017) - Decker, Christina; Wurster, Sebastian; Lazariotou, Maria; Hellmann, Anna-Maria; Einsele, Hermann; Ullmann, Andrew J; Löffler, Jürgen
Abstract: Neutrophils are essential in the first line defense against moulds. This in vitro study assessed different neutrophil effector mechanisms in the presence of clinically relevant antifungal and immunosuppressive agents. Therapeutic concentrations of liposomal amphotericin B led to reduced IL-8 and oxidative burst response to the synthetic stimulus PMA, whereas no major alterations of oxidative burst, phagocytosis, or cytokine response to germinated stages of Aspergillus fumigatus and no supra-additive effects of antifungal and immunosuppressive drugs were observed. Conventional and liposomal amphotericin B as well as voriconazole, however, led to reduced neutrophil extracellular trap formation in response to A. fumigatus germ tubes.